Formulation and characterization of poly(propylacrylic acid)/poly(lactic‐co‐glycolic acid) blend microparticles for pH‐dependent membrane disruption and cytosolic delivery. Issue 4 (21st December 2017) - Fernando, Lawrence P.; Lewis, Jamal S.; Evans, Brian C.; Duvall, Craig L.; Keselowsky, Benjamin G.
Abstract: Poly(lactic‐co‐glycolic acid) (PLGA) is widely used as a vehicle for delivery of pharmaceutically relevant payloads. PLGA is readily fabricated as a nano‐ or microparticle (MP) matrix to load both hydrophobic and hydrophilic small molecular drugs as well as biomacromolecules such as nucleic acids and proteins. However, targeting such payloads to the cell cytosol is often limited by MP entrapment and degradation within acidic endolysosomes. Poly(propylacrylic acid) (PPAA) is a polyelectrolyte polymer with the membrane disruptive capability triggered at low pH. PPAA has been previously formulated in various carrier configurations to enable cytosolic payload delivery, but requires sophisticated carrier design. Taking advantage of PPAA functionality, we have incorporated PPAA into PLGA MPs as a simple polymer mixture to enhance cytosolic delivery of PLGA‐encapsulated payloads. Rhodamine loaded PLGA and PPAA/PLGA blend MPs were prepared by a modified nanoprecipitation method. Incorporation of PPAA into PLGA MPs had little to no effect on the size, shape, or loading efficiency, and evidenced no toxicity in Chinese hamster ovary epithelial cells. Notably, incorporation of PPAA into PLGA MPs enabled pH‐dependent membrane disruption in a hemolysis assay, and a three‐fold increased endosomal escape and cytosolic delivery in dendritic cells after 2 h of MP uptake. These results demonstrate that a simple PLGA/PPAA polymer blend is readily fabricated into composite MPs, enabling cytosolic delivery of an encapsulated payload. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1022–1033, 2018.